2016
DOI: 10.1016/j.matdes.2015.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the development of three dimensional scaffolds from piezoelectric poly(vinylidene fluoride)

Abstract: Cell supports based on electroactive materials, that generate electrical signal variations as a response to mechanical deformations and vice-versa, are gaining increasing attention for tissue engineering applications. In particular, poly(vinylidene fluoride), PVDF, has been proven to be suitable for these applications in the form of films and two-dimensional membranes. In this work, several strategies have been implemented in order to develop PVDF three-dimensional scaffolds. Three processing methods, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…A highly porous microstructure is observed with the presence of pores in the same range of the sacrificial material (262–370 µm) [24]. …”
Section: Resultsmentioning
confidence: 99%
“…A highly porous microstructure is observed with the presence of pores in the same range of the sacrificial material (262–370 µm) [24]. …”
Section: Resultsmentioning
confidence: 99%
“…In this way, considering previous reports where the influence of the electric charge surface on the activity of biomaterials [25] was pointed out and discussed, it is ease to intuit that piezoelectric materials can be used to catalyze biological responses. Recent studies have been conducted in order to understand the potentialities of the polyvinylidene fluoride [(C 2 H 2 F 2 ) n or PVDF] matrix composites in human implants [26][27][28][29][30][31][32]. In this way, different biological applications have been thought for PVDF polymer, leading to different synthesis technique and sample architectures, as scaffold, for example [27].…”
Section: (Propriedades Mecânicas E Bioativas Do Compósito Pvdf-bcp) Rmentioning
confidence: 99%
“…Recent studies have been conducted in order to understand the potentialities of the polyvinylidene fluoride [(C 2 H 2 F 2 ) n or PVDF] matrix composites in human implants [26][27][28][29][30][31][32]. In this way, different biological applications have been thought for PVDF polymer, leading to different synthesis technique and sample architectures, as scaffold, for example [27]. In fact, studies conducted in cell culture have indicated some advantageous aspect of PVDF polymer for animal implants.…”
Section: (Propriedades Mecânicas E Bioativas Do Compósito Pvdf-bcp) Rmentioning
confidence: 99%
“…The mechanism of formation of different phases of PVDF films through ultrasonication and vacuum drying is explained using VIPS, which is well documented for PVDF membranes . The formation of membranes occurs as a system comprising of three components‐ that is, a combination of polymer, solvent, and nonsolvent where the solvent and nonsolvent are fully miscible here for the PVDF polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Porous PVDF structures are produced by following several protocols like vapor induced phase separation (VIPS), temperature induced phase separation (TIPS), solvent casting technique, freeze extraction, and replica molding. Such PVDF structures find applications in lithium‐ion battery separators, tissue engineering, gas separation, filtration membranes, pollutant deduction devices, and water treatment . VIPS follows a well‐documented mechanism where the PVDF films are cast by using a high boiling point solvent such as N , N ‐ Dimethylacetamide (DMAc) which evaporates slowly.…”
Section: Introductionmentioning
confidence: 99%